تصميم قطب حضري جديد ذو بعد تجاري بمنطقة عين الرومية في اطار التنمية المستدامة - ثليجي, طاهر; Ben Arfa, Kamal, Directeur de thèse (My University, 2020)
Within the framework of the great progress that the world has witnessed in recent times regarding modern architecture and a newly sustainable city, this study has been devoted to presenting a model of urban projects that fall under the sustainable development approach with a commercial dimension that aims to embody sustainability within one of the Algerian regions represented in the "Ain Roumia" This is through the embodiment and establishment of a new urban pole with a commercial dimension in the context of sustainable development, and from here we ask the question of how to create and design this project. To address this problem, I used the SWOT methodology, which revealed to me all the qualifications and problems in which the region faces, and through what you dealt with in an analytical study district of ‘’Rive gauche Paris’’ I learned about how to implement and embody the dimensions of sustainable development to create a new urban pole with a commercial dimension within the framework of sustainable development, and through what we have done, I have concluded that this project is a hour project by virtue of its contribution to reaching the fulfillment of human needs and requirements within the framework of sustainable development
Conception d’un nouveau pôle urbain a dimensioncommerciale dans la région de Ain Roumia dans le cadrede développement durable
Laghouat : Université Amar Telidji - Département d'architecture Option : Architecture et opérations urbaine